THE RELATIONSHIP OF ENGLISH ABILITY AND CAREER MOBILITY - Bejo Sutrisno; Handa Yani (Journal of English Language and Literature (JELL), 2019)
The aims of this study are to find out how the individual‘s own language competences affect career mobility and to find out how the common language acts as a facilitator for career mobility. The qualitative research method is used in this study. Interviews with personnel from the case organization, provide the opportunity to observe the views and experiences of the interviewees and to find out how they fit in to the prior research done on this subject. The empirical research on the common corporate language strategy as facilitator or barrier for career mobility implicated that the choice of English as common corporate language was generally seen as a facilitator for career mobility and as the facilitators‘ positive effect on career mobility also influenced the employee‘s subjective as well the objective measures of career success